Market Potential of Halal Products in Aceh: Case Study of Halal Industry Based on Halal Product Data 2014-2022 - Ramadhan, Ramadhan; Ulfah, Almira Keumala; Nurzianti, Rahma; Bunkes, Panetir; Kadriyani, Emilda (AL-FALAH : Journal of Islamic Economics, 2023)
Purpose: The majority of people in Aceh Province are Muslims, and the region strictly adheres to Sharia law, particularly in the halal products sector. With a focus on Aceh region, this study attempts to assess growth, obstacles, and solutions in the development of the halal business and halal goods in Indonesia.Design/Method/Approach: This study employed qualitative approaches to find material from secondary sources, including books, journals, and national statistics organizations, and to gather data.Findings: The provincial administration of Aceh has worked to establish the halal market and halal goods as an important economic driver.Originality/Values: The number of visits from visitors, particularly those from outside, is rising year after year, which reflects this expansion. The administration of Aceh province anticipates advantages from this research in the growth of the halal sector and halal goods.